Laporan Kasus: Plantar Fascitis Disertai Obesitas dengan Komsumsi Rebusan Herbal Jahe, Sereh dan Kunyit - Rianti, Riska; Makmun, Armanto (Yayasan Citra Cendekia Celebes, 2024)
Plantar Fascitis is an inflammation that occurs in the plantar fascia due to degenerative irritation of the plantar fascia where this condition can occur due to trauma or other multifactorial causes, one of which is obesity. Increased body mass can cause increased stress on the ligaments and muscles of the foot when bearing body weight which ultimately causes microtrauma. For treatment of plantar fascitis in the form of pharmacological and non-pharmacological therapies in reducing pain intensity, namely by using herbal therapy with plants that can be used as alternative medicine. Currently there are various plants that can be used for alternative medicine including ginger, lemongrass and turmeric. This journal aims to discuss case reports related to the consumption of herbal decoctions of ginger, lemongrass and turmeric as analgesics in plantar fascitis patients. Based on some literature, it is found that jehe has hot, bitter and aromatic properties of oleoresin, gingenol, shagaol and zingeron which have the ability as anti-inflammatory and analgesic. Lemongrass and turmeric contain essential oils that are chemical in nature and have pharmacological effects as anti-inflammatory and analgesic. The conclusion obtained in this case report is that the provision of pharmacological therapy and combined with non-pharmacological therapy in the form of stretching and giving herbal plants with ginger, lemongrass and turmeric decoction results in reducing the intensity of pain experienced by patients.